Unusual association of transposition of great arteries with infradiaphragmatic pulmonary venous return - Giuseppe Scrascia; Anna Maria Pia Grimaldi; Dario Troise; Gabriele Scalzo (Wolters Kluwer Medknow Publications, 2020)
A 21-day-old baby with transposition of the great arteries with intact ventricular septum, infradiaphragmatic totally anomalous pulmonary venous connection, and atrial septum defect underwent combined arterial switch operation, totally anomalous venous connection repair, and atrial septum defect closure, using a right-sided approach and temporary pulmonary veins occlusion, with no postoperative and 6-months follow-up complications. Complete anatomical correction is the most conceivable treatment for this unusual pathology; right-sided approach instead lifting the heart toward the right pleural cavity to perform left atrium-to-pulmonary veins anastomosis limits heart displacement and avoids nonphysiological three-dimensional alterations; moreover, ligation and division of vertical vein allow to obtain more tissue for anastomosis; temporary occlusion of pulmonary veins while performing anastomosis is a simple procedure that allows to avoid deep hypothermic circulatory arrest or low flow systemic perfusion. Combination of these details facilitates intra- and postoperative management, especially in combined demanding cases.